Open forensic science*. Issue 1 (9th July 2019) - Chin, Jason M; Ribeiro, Gianni; Rairden, Alicia
Abstract: The mainstream sciences are experiencing a revolution of methodology. This revolution was inspired, in part, by the realization that a surprising number of findings in the bioscientific literature could not be replicated or reproduced by independent laboratories. In response, scientific norms and practices are rapidly moving towards openness. These reforms promise many enhancements to the scientific process, notably improved efficiency and reliability of findings. Changes are also underway in the forensic. After years of legal-scientific criticism and several reports from peak scientific bodies, efforts are underway to establish the validity of several forensic practices and ensure forensic scientists perform and present their work in a scientifically valid way. In this article, the authors suggest that open science reforms are distinctively suited to addressing the problems faced by forensic science. Openness comports with legal and criminal justice values, helping ensure expert forensic evidence is more reliable and susceptible to rational evaluation by the trier of fact. In short, open forensic science allows parties in legal proceedings to understand and assess the strength of the case against them, resulting in fairer outcomes. Moreover, several emerging open science initiatives allow for speedier and more collaborative research.